Research progress on the hydrogen permeation behavior of the nuclear waste container–A mini review - Qichao Zhang; Qichao Zhang; Yishan Jiang; Binbin Zhang; Jizhou Duan; Xin Zhao; Juna Chen (Frontiers in Materials, 2022)
A large amount of nuclear waste produced in the process of nuclear energy utilization has always been a key problem to be solved urgently for nuclear safety. At present, “deep geological disposal” is a feasible method and is generally accepted by many countries. It is a “multi-barrier system” composed of an artificial barrier, including the solidified waste body, outer packaging material, buffer backfill material, and a natural barrier including the surrounding rock. During deep geological disposal, a near-field environment, where the corrosion of a container could happen, is formed with continuous groundwater infiltration and the release of much heat energy in the process of nuclear waste decay and fission. At the same time, the environment will become a long-term reduction place because of the gradual consumption of the initially retained oxygen. The hydrogen evolution reaction is dominant, so unpredictable hydrogen embrittlement of the container materials could happen due to hydrogen absorption and penetration. This study summarizes the possibility of hydrogen embrittlement of carbon steel, titanium, and their alloys from three aspects, namely, hydrogen solubility, diffusion coefficient, and hydrogen embrittlement, which provides a theoretical basis for predicting the container life in a large time scale.